Collagen-Based Fillers as Alternatives to Cyanoacrylate Glue for the Sealing of Large Corneal Perforations. Issue 5 (May 2018) - Samarawickrama, Chameen; Samanta, Ayan; Liszka, Aneta; Fagerholm, Per; Buznyk, Oleksiy; Griffith, May; Allan, Bruce
Abstract : Purpose: To describe the use of collagen-based alternatives to cyanoacrylate glue for the sealing of acute corneal perforations. Methods: A collagen analog comprising a collagen-like peptide conjugated to polyethylene glycol (CLP-PEG) and its chemical crosslinker were tested for biocompatibility. These CLP-PEG hydrogels, which are designed to act as a framework for corneal tissue regeneration, were then tested as potential fillers in ex vivo human corneas with surgically created full-thickness perforations. Bursting pressures were measured in each of 3 methods (n = 10 for each condition) of applying a seal: 1) cyanoacrylate glue with a polyethylene patch applied ab externo (gold standard); 2) a 100-μm thick collagen hydrogel patch applied ab interno, and 3) the same collagen hydrogel patch applied ab interno supplemented with CLP-PEG hydrogel molded in situ to fill the remaining corneal stromal defect. Results: Cyanoacrylate gluing achieved a mean bursting pressure of 325.9 mm Hg, significantly higher than the ab interno patch alone (46.3 mm Hg) and the ab interno patch with the CLP-PEG filler (86.6 mm Hg). All experimental perforations were sealed effectively using 100 μm hydrogel sheets as an ab interno patch, whereas conventional ab externo patching with cyanoacrylate glue failed to provide a seal in 30% (3/10) cases. Conclusions: An ab interno patch system using CLP-PEG hydrogels designed to promote corneal tissue regeneration may be a viable alternative to conventional cyanoacrylate glue patching for the treatment of corneal perforation. Further experimentation and material refinement is required in advance of clinical trials. Abstract : Supplemental Digital Content is Available in the Text.